Potentials for a socially equitable and ecologically sustainable society - Fritz, Martin; Koch, Max (Ökologisches Wirtschaften - Fachzeitschrift, 2014)
A steady state economy needs indicators that capture ecological sustainability, social inclusion and quality of life based on both objective and subjective data. Interrelations between indicators and country comparisons show the potential of increasing prosperity without raising material consumption.